Emergence of interpersonal helping in times of crises: a theoretical model of prosperity and eradication of interpersonal helping in organizations. Issue 10 (9th November 2020) - Chou, Shih Yung; Ramser, Charles; Chang, Tree; Han, Bo
Abstract : Purpose: The purpose of this article is to develop a cross-level, theoretical model describing the process by which interpersonal helping becomes conspicuous, as well as the process by which interpersonal helping subsequently prospers or becomes eradicated in the organization. Design/methodology/approach: A theoretical analysis was performed by drawing upon various management-related theories. Findings: We propose that organizational crises foster the emergence of interpersonal helping. Additionally, the positive relationship between organizational crises and interpersonal helping is stronger (or weaker) when individuals possess higher levels of other-oriented (or self-oriented) motives. Furthermore, we propose that a sympathetic climate at the unit level and employee job crafting at the individual level result in the prosperity of interpersonal helping, whereas interpersonal helping is eradicated by a sarcastic atmosphere at the unit level and citizenship pressure at the individual level. Originality/value: Theoretically, we advance the literature by providing future research with a theoretical base for understanding interpersonal helping from a temporal and cross-level perspective. Practically, this article offers some managerial recommendations that help managers nurture interpersonal helping in organizations effectively.